Inovasi Produk Alam yang Dapat Dimanfaatkan untuk Mengobati Jerawat - Masayu Azizah; Nilda Lely; Agnes Rendowaty; Ade Arinia Rasyad; Ema Ratna Sari; Erjon Erjon; Dewi Patmayuni; Lilik Pranata; Masayu Rosyidah (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2025)
Acne is a common skin problem experienced by the community. Characterized by red spots, inflammation, and blackheads, or clogged pores, on the face, neck, and back. Acne is a scary specter for teenagers, especially during puberty, where teenagers want to look their best and glowing, this will be a big problem if the teenager has acne, it will reduce their level of self-confidence, so there is a need for education for students. The purpose of this PkM activity is to introduce students to the innovation of natural products that can be used to treat acne. The method of activity carried out by means of education and assistance in the Innovation of Natural Products That Can Be Used to Treat Acne. The education participants were students of Madrasah Ibtidaiyah and SMP Yayasan Ummul Quro Al-Hamidiyah totaling 50 students. The activity was carried out on Thursday, December 19, 2024. The results of the activity showed that the students were very enthusiastic about participating, and the students had understood what was explained by the speaker. The conclusion of the activity shows that there was an increase in student knowledge after being given education about Natural Product Innovations That Can Be Used to Treat Acne.